Enhancing Nurses' Proficiency: A Study on the Impact of Caring Education Booklets - Anggun Nur Alina; Jebul Suroso (Proceedings Series on Health & Medical Sciences, 2024)
Background: Caring is a common phenomenon and a crucial component in delivering nursing care. In providing quality nursing care, in addition to caring, nurses also require adequate knowledge to provide optimal nursing care. One way to enhance knowledge is by using media that are engaging and easily comprehensible for nurses. Method: A pre-experimental research design with a non-randomized and post-test without a control group design was employed. The study was conducted in July 2023 in the Internal Medicine Ward of the hospital, involving a total of 32 respondents selected through a total sampling technique. The research instrument used was a questionnaire. Data were analyzed using the Spearman rank correlation test. Results: The research results indicated that the majority of nurses were aged 35 years, with 17 female respondents (53.1%), and 19 respondents (59.4%) having a Ners degree as their latest education. The average knowledge score of nurses regarding caring during nursing care before receiving caring training was 16.25, and after receiving caring training, it increased to an average of 19.28. After conducting the Spearman rank correlation test, a p-value of 0.016 was obtained (p0.05). Conclusion: There is an influence of caring education using booklets on nurses' knowledge while providing nursing care to patients in the Internal Medicine Ward of Ajibarang Regional General Hospital.